2009
DOI: 10.1002/biof.22
|View full text |Cite
|
Sign up to set email alerts
|

Vitagenes, cellular stress response, and acetylcarnitine: Relevance to hormesis

Abstract: Modulation of endogenous cellular defense mechanisms via the stress response signaling represents an innovative approach to therapeutic intervention in diseases causing chronic damage, such as neurodegeneration and cancer. Protein thiols play a key role in redox sensing, and regulation of cellular redox state is crucial mediator of multiple metabolic, signaling, and transcriptional processes. Maintenance of optimal long-term health conditions is accomplished by a complex network of longevity assurance processe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
114
0

Year Published

2010
2010
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 131 publications
(118 citation statements)
references
References 152 publications
(253 reference statements)
4
114
0
Order By: Relevance
“…HO is present in various tissues with the highest activity in the brain, liver, spleen, and testes. There are three isoforms of heme oxygenase, HO-1 or inducible isoform [13,16,22], HO-2 or constitutive isoform [49], and the recently discovered HO-3, cloned only in rat to date [50]. Elevation of HO-1 expression and activity in MS is probably due to elevated oxidative stress.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…HO is present in various tissues with the highest activity in the brain, liver, spleen, and testes. There are three isoforms of heme oxygenase, HO-1 or inducible isoform [13,16,22], HO-2 or constitutive isoform [49], and the recently discovered HO-3, cloned only in rat to date [50]. Elevation of HO-1 expression and activity in MS is probably due to elevated oxidative stress.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, cytokines, immunoglobulins, and complement complexes may elicit a survival response in the oligodendrocytes, involving the induction of endogenous heat shock proteins and other protective molecules, which indicates that redox systems and therefore the oxidant/antioxidant balance in these cells are of great importance in MS [9][10][11][12]. The adaptation and survival of cells and organisms requires the ability to sense proteotoxic insults and to coordinate protective cellular stress response pathways and chaperone networks related to protein quality control [13]. Despite the abundance and apparent capacity of chaperones and other components of homeostasis to restore folding equilibrium, brain cells appears poorly adapted for chronic proteotoxic stress which increases in neurodegenerative diseases such as MS [14].…”
Section: Introductionmentioning
confidence: 99%
“…(97-100, 105-108, 281). These include members of the Hsp family, such as heme oxygenase-1 and Hsp72, sirtuins, and the thioredoxin=thioredoxin reductase system (103,106,107). Recent studies have shown that the HSR contributes to establishing a cytoprotective state in a wide variety of human diseases, including inflammation, cancer, aging, and neurodegenerative disorders.…”
Section: Proteotoxicity Cellular Stress Response and The Vitagementioning
confidence: 99%
“…Cellular stress response (Fig. 4) requires the activation of pro-survival pathways that, under control of protective genes called vitagenes (99,100,(106)(107)(108), result in the production of molecules (Hsps, glutathione, and bilirubin) endowed with antioxidant and antiapoptotic activities. Generally, molecular chaperones help hundreds of signaling molecules to keep their activation-competent state, and regulate various signaling processes ranging from signaling at the plasma membrane to transcription.…”
Section: Proteotoxicity Cellular Stress Response and The Vitagementioning
confidence: 99%
“…Moreover, in addition to phosphorylation, it appears that Snitrosylation of SIRT1 impairs the catalytic activity of enzymes via a nitrosylated glyceraldehyde-3-phosphate dehydrogenasemediated process [12]. Additionally, thioredoxin (Trx) regulates cellular redox balance through reversible oxidization of its redoxactive cysteine residues (-Cys-Gly-Pro-Cys-), which can mediate protein S-denitrosylation [13][14][15] and hence the activity of sirtuins. The deacetylase domain of sirtuins consists of approximately 250 amino acids, differentiated by divergent N-and Cterminal extensions [16].…”
Section: Introductionmentioning
confidence: 99%